2014
DOI: 10.1021/np400953n
|View full text |Cite
|
Sign up to set email alerts
|

Withanolides from Physalis hispida

Abstract: Nine new withanolides (1-9), withahisolides A-I, were isolated along with nine known compounds (10-18) from the aerial parts of Physalis hispida. The structures of 1-9 were elucidated through a variety of spectroscopic techniques, while the structures of 1 and 2 were confirmed by X-ray crystallographic analysis. Compounds 1-3 are the first withanolides with nonaromatic six-membered ring D moieties. In addition, withanolide 8 represents a novel withanolide skeleton due to the absence of a C-13-C-17 bond within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…From this species, several withanolides have been reported possessing either the normal or modified skeletons (ring-D aromatic). [6][7][8][9][10][11][12] N. physalodes is considered an ornamental plant possessing insect repellent properties. In fact, its main constituent named as nicandrenone showed antifeedant activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From this species, several withanolides have been reported possessing either the normal or modified skeletons (ring-D aromatic). [6][7][8][9][10][11][12] N. physalodes is considered an ornamental plant possessing insect repellent properties. In fact, its main constituent named as nicandrenone showed antifeedant activity.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8]13 In a continuing effort to isolate active compounds from the Brazilian Solanaceae, the acetone extract from N. physalodes was investigated. As results, five new withanolides (15-oxonicaphysalin B (1), 6β,7α-dihydroxynicandrenone 10 (2), 24α ,25β -dihydroxy-nicandrenone-2 (3 ) and a mixture of the epimers 17-(1α/1β-methylpropanone)-nicandrenone (4a/4b)), in addition to nicandrenone-10 (5), nicandrenone (6), nicandrenone-7 (7), 10 nicandrenone-2 (8), 7 nicaphysalin B (9), 9 and 26R-withahisolide G (10), 12 were isolated. The isolated compounds were evaluated for their antibacterial and antifungal effects.…”
Section: Introductionmentioning
confidence: 99%
“…63 It was observed that both the OH-17α and OH-17β shield the γpositioned C-12 (∼7−9 ppm decrease), as demonstrated by the 13 C NMR comparison of steroids 65−87: androstanes [65 64 and its 17β-hydroxy derivatives (43 51,64 and 66 64 )], pregnane (67); 65 cholestanes [68, 65 and the related 17β-hydroxy (69) 66 and 17α-hydroxy (70) 67 derivatives]; and withanolides (31,34,37,58, and 71−87) (Figure 3, Tables S1, S3, and S4, Supporting Information). This analysis compared the data of each classic withanolide against their corresponding 17-hydroxy derivatives: (1) withanolide B (37) 46 and the corresponding 17α-hydroxy (31) 16 and 17β-hydroxy (34) 23,24 derivatives; (2) withanolide A (71) 16 and its 17α-hydroxy derivative (72); 16 (3) daturalactone-4 (73) 68 and its 17β-hydroxy derivative (74); 16 (4) withaferin A (58) 59 against its 17α-hydroxy derivative (75); 69 (5) 5β,6β-epoxy-1-oxowitha-3,24-dienolide (76) 59 against jaborosalactone L (77); 70 (6) 16α-acetoxy-5β,6β-epoxy-1-oxowitha-2,24-dienolide (78) 71 and its 17αhydroxy derivative (79); 71 (7) 5,6-deoxywithaferin A (80) 72 against its 17α-hydroxy derivative (81); 73 (8) 27-hydroxy-1oxowitha-2,5,24-trienolide (82) 74 against cilistol A (83); 75 (9) 5α,6β-dihydroxywithaferin A (84) 43,76 against cilistadiol (85); 77 and (10) 6α-chloro-5β-hydroxywithaferin A (86) 10 against 6αchloro-5β,17α-dihydroxywithaferin A (87). 10 In addition, there are insignificant chemical shift differences (<2 ppm) observed on the carbons of the steroid nucleus caused between the αand β-orientation of the 17-hy...…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…bipinnatif ida (Dunal) Reiche, 4 Physalis coztomatl Dunal, 5 P. hispida (Waterf.) Cronquist, 6 P. longifolia Nutt., 7,8 Vassobia brevif lora (Sendtn.) Hunz., 9 and Withania somnifera (L.) Dunal.…”
mentioning
confidence: 99%
“…In the past decade, with the rapid development and application of various separation techniques and spectral analysis techniques, especially nuclear magnetic resonance spectroscopy, the research speed of the compounds in the solanaceae has been greatly accelerated, and its structural research has made great progress. Up to now, more than 900 kinds of withanolides have been separated from the whole world [5,6].…”
mentioning
confidence: 99%